PENGARUH CORPORATE GOVERNANCE TERHADAP GREEN BANKING DISCLOSURE (STUDI PADA PERUSAHAAN PERBANKAN DI INDONESIA YANG TERDAFTAR DI BEI PERIODE 2018 – 2020) - Petro, San; Octavia, Rini; Diarsyad, Muhammad Ichsan (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
This research aims to analyze the influence of Corporate Governance on Green Banking Disclosure in banking companies listed on the Indonesia Stock Exchange during the period of 2018 - 2020. Corporate governance plays a crucial role in ensuring transparency and accountability within companies, as well as supporting their efforts in implementing sustainable and responsible business practices towards the environment. In this study, Corporate Governance is measured through three variables: Board of Commissioners, Independent Commissioners, and Institutional Ownership. The Board of Commissioners is considered as one of the institutions responsible for decisionmaking within the company. The number of board members is an important indicator in this research, as a larger board size allows for diverse perspectives and expertise to be applied in the decision-making process. Additionally, Independent Commissioners are also a significant factor in maintaining the independence and integrity of the company’s oversight. In this study, the proportion of Independent Commissioners compared to the total number of commissioners is used as a measure of their presence and independence. Institutional Ownership is another variable of interest in this research. Institutional ownership reflects the participation and involvement of financial institutions and institutional investors in the ownership of company shares. The percentage of institutional ownership in relation to the total outstanding shares is measured to gain insights into the extent of financial institutions’ role in decision-making and oversight within the company. Green Banking Disclosure is the main focus of this study. Green Banking encompasses banking practices that prioritize environmental sustainability. Green Banking Disclosure is measured using the Green Banking Disclosure Index (GBDI), which covers various aspects such as environmental risk management, sustainable financing, and other environmental initiatives. To test the relationship between these variables, the researcher employs multiple linear regression analysis. The data used in this study consists of 96 observations, involving 32 banking companies each year. The data is analyzed using the Statistical Package for Social Sciences (SPSS) software to generate generalizable findings.The results of this study indicate that the Board of Commissioners has a significant positive influence on Green Banking Disclosure in banking companies listed on the Indonesia Stock Exchange during the period of 2018 - 2020. This suggests that a stronger composition and role of the Board of Commissioners in decision-making lead to higher levels of disclosure of environmentally friendly business practices. However, the study did not find a significant relationship between Independent Commissioners and Green Banking Disclosure, and it found that Institutional Ownership has a significant negative influence on Green Banking Disclosure. These findings provide a deeper understanding of the importance of the role and composition of Corporate Governance in promoting the disclosure of sustainable business practices in banking companies in Indonesia. Keywords: Board of Commissioners; Independent Commissioners; Institutional Ownership; Green Banking Disclosure